Credit margin of investment in the agricultural sector and credit fungibility: the case of smallholders of district Shikarpur, Sindh, Pakistan - Abbas Ali Chandio; Yuansheng Jiang; Abdul Rehman (Financial Innovation, 2018)
Abstract Background This study examines the access to credit, credit investment, and credit fungibility for small-holder farmers and medium- and large-scale farmers in the agricultural sector of the Shikarpur District of Sindh, Pakistan. Methods A standardized questionnaire was used to collect data from 87 farmers in the Shikarpur District. We investigated the availability of credit and the use of credit fungibility by farmers with small-, medium-, and large-scale holdings by applying a credit fungibility ratio and an ANOVA technique. The factors that influence the farmers’ access to agricultural credit were analyzed using a probit regression model. Results The results revealed that farmers in both study groups used some amount of their agricultural credit for non-agricultural activities. Further, the results of the probit regression analysis showed that formal education, farming experience, household size, and farm size had a positive and significant influence on the farmers’ access to agricultural credit. Conclusion Based on these findings, our study suggests that a strong monitoring of farmers is needed in the study area.